Parisian surgeon's secret child - MacKay, Sue (Susan) (Harlequin medical romance, 2025)
Back in Paris after fifteen months abroad, nurse Camille must finally tell renowned surgeon Etienne that their brief relationship resulted in a baby girl! Coming from a wealthy background, Etienne has frequently been targeted for money, including being lied to about fatherhood. So Camille doesn't expect him to believe her, until he meets Elyna, and she can see the recognition in his eyes. As they bond over their daughter, Camille increasingly wishes they could be a family-but can Etienne trust anyone to love him for himself...